Efficient combined fuzzy logic and LMS algorithm for smart antenna - Miry, Mohammed Hussein; Mary, Ali Hussien (Telkomnika, 2023)
Received Aug 07, 2022 Revised Jan 02, 2023 Accepted Feb 16, 2023 Keywords: Fuzzy logic LMS algorithm Smart antenna ABSTRACT The smart antennas are broadly used in wireless communication. INTRODUCTION The smart antenna technique [l]-[3] is an integration of the array of antenna together with the digital signal processing in order to automatically optimize the radiation pattern in response to environment of the signal. [...]the step size assignment is usually a trade-off between rapid convergence and low steady-state fluctuations. In conventional LMS (C-LMS) algorithm, ı step size is fixed parameter at all iterations and limited by Horowitz Serine equation [26]: 0 < u < - (6) ^ 3NPX v ' While JV represents tap weight number of the adaptive filter, whereas Px identifies the input power.